2020
DOI: 10.1016/j.psj.2020.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Achyranthes bidentata polysaccharides on performance, immunity, antioxidant capacity, and meat quality in Pekin ducks

Abstract: This study was conducted to evaluate the effects of Achyranthes bidentata polysaccharide ( ABP ) on growth performance, antioxidant capacity, immune function, relative organ weight, ileal microflora, and meat quality in Pekin ducks. A total of 1,200 female 1-day-old Pekin ducklings (51.2 ± 0.2 g) were blocked based on body weight ( BW ) and randomly allocated into 3 treatments with 10 replicates of 40 birds each. The experiment lasted for 6 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Also, Yang et al (2019a) reported that both Astragalus polysaccharide and ginseng polysaccharide improves the ADG and FCR and reduced diarrhea rate of piglets. In poultry, polysaccharides were shown to positively influence growth performance ( Guo et al., 2004 ; Abdullahi et al., 2016 ; Ao and Kim, 2020 ), but this finding was not confirmed by Chen et al. (2003) .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Also, Yang et al (2019a) reported that both Astragalus polysaccharide and ginseng polysaccharide improves the ADG and FCR and reduced diarrhea rate of piglets. In poultry, polysaccharides were shown to positively influence growth performance ( Guo et al., 2004 ; Abdullahi et al., 2016 ; Ao and Kim, 2020 ), but this finding was not confirmed by Chen et al. (2003) .…”
Section: Discussionmentioning
confidence: 92%
“…Polysaccharides—high-molecular-weight long-chain carbohydrates composed of monosaccharides, such as aldose or ketose, bound together by glycosidic linkages—are widely present in plants, animals, and microorganisms ( Ayeka et al., 2016 ; Huang et al., 2017 ). Plant polysaccharides are rich in varieties, wide in sources, and easily extracted from plant flower, seeds, roots, stems, and leaves ( Ao and Kim, 2020 ). It is generally considered that plant polysaccharides derived from Chinese herbs have remarkable pharmacological capacities including, among others, immunomodulatory, antioxidant, and antitumor functions ( Xiong et al., 2019 ; Chen et al., 2016 ; Li et al., 2019) .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, HS exposure downregulated the duodenal mucosal expression levels of antioxidant enzyme genes and Nrf2 . Because of the antioxidant effect of natural polysaccharides in poultry [ 19 , 30 , 31 , 48 ], the alleviation effects of dietary supplementation of ADP on oxidative stress of the duodenal mucosa in broilers under HS should be explored. The results showed that dietary ADP supplementation improved the antioxidant capacity in the duodenum of broilers under HS, which was connected with the modulation of the Nrf2 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Achyranthes bidentata Blume (named Huai Niu Xi, a member of the Amaranthaceae family), a traditional Chinese medicinal herb, is widely used in China, Korea, and Japan for its function of nourishing the kidney and liver and strengthening muscles and bones (Ou et al, 2018;Ao and Kim, 2020). The polysaccharide (ABPS) is extracted from A. bidentata.…”
Section: Introductionmentioning
confidence: 99%
“…The polysaccharide (ABPS) is extracted from A. bidentata. Pharmacological studies have demonstrated that ABPS has multiple functions, such as antiosteoporosis, anti-inflammatory, antioxidant, antiallergic, and immunomodulatory (Yan et al, 2019;Ao and Kim, 2020). However, the mechanism of the immunomodulatory activity of ABPS is unclear.…”
Section: Introductionmentioning
confidence: 99%